STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI GURU MISMATCH MELALUI PENDIDIKAN DAN PELATIHAN - SYARMAN WADI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to, 1) teacher competency mismatch, 2) principal's strategy in improving teacher mismatch competency This study uses a descriptive qualitative approach by looking directly at the field regarding the methods applied. Data collection techniques through observation, interviews and documentation. in analyzing the data obtained, the researcher used a model of data collection, data reduction, data presentation and conclusions. Meanwhile, to check the validity of the data using credibility, transferability, dependability and confirmability. The results of this study indicate that the factors that cause teacher mismatch are the lack of Madrasah finance, the lack of teachers who have diplomas in accordance with what is needed, as pioneers in the establishment of madrasas, the small number of students and the existence of foundation intervention. The mismatch teacher competence itself is still not good in terms of learning design. Meanwhile, the madrasa principal's strategy to improve mismatch teacher competence is through education and training through on the job site and off the job site schemes.